Flavonoid-profile determination for a hypoglycemic collection by high-performance liquid chromatography - A. M. Kutovaya; V. N. Davydova; I. B. Perova; K. I. Eller (Тонкие химические технологии, 2020)
Objectives. Herbal hypoglycemic drugs complement the conventional approach to the treatment of type-2 diabetes based on the use of synthetic prescription drugs. However, their scientifically based application and standardization are limited due to inadequate and often outdated information on their chemical composition. Accordingly, we have developed a hypoglycemic collection (HGС) consisting of common bean pods (Phaseolus vulgaris L.), bilberry shoots (Vaccinium myrtillus L.), galega herb (Gallega officinalis L.), common knotgrass herb (Polygonum aviculare L.), burdock roots (Arctium lappa L.), and cinnamon rose hips (Rosa cinnamomea L.). According to a number of researchers, the antidiabetic properties of these herbs are largely due to the presence of polyphenolic compounds, especially flavonoids. The aim of this study was to determine the profile of flavonoids in the HGС and in its total dry extract (TDE).Methods. The study was performed by reverse-phase high-performance liquid chromatography with diode array and mass spectrometric detection.Results. Nine individual flavonol glycosides—derivatives of myricetin, quercetin, kaempferol and kaempferide—were identified in the HGC and the TDE. The main flavonol glycosides in the studied objects were robinin and kaempferol-3-glucuronide, the contents of which in the HGC were 2.09 and 2.22 mg/g, in the TDE 4.85 and 3.84 mg/g, respectively. The other flavonol glycosides were determined in the HGC and its TDE at significantly lower concentrations.Conclusions. The method developed in the study can be used to standardize HGCs and estimate their pharmacological activities.